Lithium manganese iron phosphate positive electrode material, preparation method thereof and electrochemical device

By doping magnesium and covering niobium into the lithium manganese iron phosphate positive electrode material, the problems of its conductivity and capacity are solved, the performance and cycle stability of the battery are improved, and it is suitable for high-performance batteries.

CN119218963APending Publication Date: 2024-12-31NANTONG RESHINE NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411463525.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The poor electron and ion conductivity of the lithium manganese iron phosphate (LMFP) cathode material limits its performance in high-power applications, and the Jahn-Teller distortion of manganese ions in the oxidized state Mn3+ affects the lithium ion diffusion kinetics. It affects the overall performance of the battery.

Method used

Using two-stage grinding and two-stage sintering processes, magnesium is doped into the body phase of the LMFP positive electrode material, and niobium is coated on the surface to form a synergistic structure with bulk phase doped magnesium and surface coated on the surface, which reduces Jahn- Teller effect and improve surface ion conductivity.

Benefits of technology

The electronic conductivity, structural stability and specific capacity of LMFP positive electrode materials are improved, the rate performance and cyclic performance are enhanced, and the problems of conductivity and low capacity are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218963A_ABST
    Figure CN119218963A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium manganese iron phosphate positive electrode material and a preparation method thereof, and an electrochemical device, the preparation method of the lithium manganese iron phosphate positive electrode material comprises the following steps: mixing a manganese source, an iron source, a first phosphorus source, a lithium source, a first carbon source and a magnesium source, and carrying out primary grinding to obtain a first slurry; carrying out primary sintering on the first slurry to obtain a lithium manganese iron phosphate precursor; mixing the lithium manganese iron phosphate precursor, a second phosphorus source, a second carbon source and a niobium source, and performing secondary grinding to obtain second slurry; the second slurry is subjected to secondary sintering, the lithium manganese iron phosphate positive electrode material is obtained, the magnesium element exists in a bulk phase of the lithium manganese iron phosphate positive electrode material in a doping mode, and the niobium element exists in a coating layer of the lithium manganese iron phosphate positive electrode material in a coating mode. According to the preparation method, magnesium and niobium are co-doped and coated, and through the synergistic effect of magnesium and niobium, the electron and ion conductivity, the specific capacity and the cycle performance of the lithium manganese iron phosphate positive electrode material are jointly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy, and specifically to a lithium iron manganese phosphate positive electrode material and a preparation method and an electrochemical device thereof. Background Art

[0002] As the global demand for renewable energy and electric vehicles continues to increase, the scarcity, cost and environmental impact of battery materials have attracted widespread attention. Especially in terms of lithium-ion battery cathode materials, although traditional nickel-cobalt-manganese (NCM) and nickel-cobalt-aluminum (NCA) materials have excellent energy density, the high cost and environmental impact of the rare metal resources they require have raised questions about their sustainability. In this context, lithium manganese iron phosphate (LMFP) as a new cathode material has attracted much attention due to its cheap raw materials, excellent cycle stability and high thermal safety.

[0003] Although LMFP cathode materials show great potential in improving energy density, they still have some drawbacks. For example, LMFP has poor electronic and ionic conductivity, which limits its performance in high-power applications. In addition, manganese ions in the oxidized state Mn 3+ The Jahn-Teller distortion under the influence of the kinetics of the Li-ion diffusion in the LMFP cathode material will lead to slow Li-ion diffusion in the LMFP cathode material, thus affecting the overall performance of the battery. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a lithium manganese iron phosphate (LMFP) positive electrode material.

[0005] In addition, the embodiments of the present application also provide a LMFP positive electrode material prepared by the aforementioned preparation method and an electrochemical device using the LMFP positive electrode material.

[0006] The present application provides a method for preparing a LMFP positive electrode material, the preparation method comprising the following steps: Mixing a manganese source, an iron source, a first phosphorus source, a lithium source, a first carbon source and a magnesium source and grinding them once to obtain a first slurry; The first slurry is sintered once to obtain a LMFP precursor; The LMFP precursor, the second phosphorus source, the second carbon source and the niobium source are mixed and subjected to secondary grinding to obtain a second slurry; and The second slurry is subjected to secondary sintering to obtain the LMFP positive electrode material, wherein the magnesium element exists in the bulk phase of the LMFP positive electrode material in the form of doping, and the niobium element exists in the coating layer of the LMFP positive electrode material in the form of coating.

[0007] In some possible embodiments, the molar ratio of magnesium element to lithium element in the first slurry is (0.002-0.006):1; and / or The molar ratio of niobium element to lithium element in the second slurry is (0.005-0.02):1.

[0008] In some possible embodiments, the primary grinding speed is 500 rpm to 800 rpm; and / or The particle size Dv50 of the first slurry is 0.4 μm-1.0 μm.

[0009] In some possible embodiments, the secondary grinding has a rotation speed of 500 rpm to 800 rpm; and / or The particle size Dv50 of the second slurry is 0.2 μm to 0.8 μm.

[0010] In some possible embodiments, the conditions of the primary sintering include: a temperature of 500° C. to 700° C., a time of 6 to 12 hours, and a heating rate of 2° C. / min to 5° C. / min; and / or The conditions of the secondary sintering include: a temperature of 700° C. to 850° C., a time of 6 to 12 hours, and a heating rate of 2° C. / min to 5° C. / min.

[0011] An embodiment of the present application also provides a LMFP positive electrode material, which is prepared by the aforementioned method for preparing the LMFP positive electrode material. The LMFP positive electrode material includes a positive electrode active material and a coating layer located on the surface of the positive electrode active material, wherein the positive electrode active material is doped with magnesium and the coating layer contains niobium.

[0012] In some possible embodiments, the niobium element is present in the form of LiNbO 3 .

[0013] In some possible embodiments, based on the total mass of the LMFP positive electrode material being 100%, the mass content of the magnesium element is 0.3% to 0.9%.

[0014] In some possible embodiments, based on the total mass of the LMFP positive electrode material being 100%, the mass content of the niobium element is 0.1%-0.5%.

[0015] An embodiment of the present application also provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes the aforementioned LMFP positive electrode material.

[0016] Compared with the prior art, the LMFP positive electrode material provided in the embodiment of the present application is formed by a two-stage grinding and two-stage sintering process. The first grinding and the first sintering are used to dope magnesium in the bulk phase of the LMFP positive electrode material; the second grinding and the second sintering are used to form a coating layer containing niobium on the surface of the LMFP positive electrode material, thereby obtaining a LMFP positive electrode material with a doping-coating synergistic effect of magnesium doping in the bulk phase and niobium coating on the surface. The magnesium doping in the bulk phase reduces the Mn 3+ The Jahn-Teller effect promotes the 2+ / 3+ The redox reaction enhances the electronic conductivity and structural stability of the LMFP cathode material; at the same time, the surface coating of niobium effectively improves the surface ion conductivity of the LMFP cathode material, thereby improving the specific capacity of the LMFP cathode material. The magnesium element in the bulk phase and the niobium element in the surface phase work synergistically to improve the electronic and ionic conductivity, specific capacity and cycle performance of the LMFP cathode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A process flow chart of the method for preparing the lithium iron manganese phosphate positive electrode material provided in an embodiment of the present application.

[0018] Figure 2 A schematic diagram of the structure of the electrochemical equipment of the lithium manganese iron phosphate positive electrode material provided in an embodiment of the present application.

[0019] Figure 3 A charge and discharge comparison chart of a battery prepared with the lithium manganese iron phosphate positive electrode material provided in Example 1 and Comparative Examples 1-3 of the present application.

[0020] Figure 4 A comparison chart of the cycle capacity retention rates of batteries prepared with the lithium manganese iron phosphate positive electrode materials provided in Example 1 and Comparative Examples 1-3 of the present application.

[0021] Figure 5 This is a scanning electron microscope image of the lithium iron manganese phosphate positive electrode material provided in Example 1 of the present application. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0023] See also Figure 1 As shown, the present application embodiment provides a method for preparing a lithium manganese iron phosphate (LMFP) positive electrode material, the preparation method comprising the following steps: Step S1, mixing a manganese source, an iron source, a first phosphorus source, a lithium source, a first carbon source and a magnesium source and grinding them once to obtain a first slurry.

[0024] In some embodiments, the molar ratio of lithium element to transition metal element (Mn and Fe) and phosphorus element in the first slurry can be (1.010~1.045):1:(0.96~0.98), which is beneficial to control the ratio of each element in the final LMFP positive electrode material within a reasonable range, so as to improve the electrochemical performance, stability and energy density of the LMFP positive electrode material.

[0025] In some embodiments, the molar ratio of magnesium to lithium in the first slurry may be (0.002-0.006):1, which is beneficial to further improve the doping effect of magnesium and enhance the conductivity and cycle stability of the material. The molar ratio may further be (0.003-0.005):1, and may be 0.002:1, 0.003:1, 0.004:1, 0.005:1 or 0.006:1, etc.

[0026] In some embodiments, the manganese source, iron source, first phosphorus source, lithium source, first carbon source and magnesium source can be dissolved in a first solvent and mixed evenly before grinding, which can effectively improve the mixing and grinding effect. Furthermore, the first solvent can be water.

[0027] In some embodiments, the primary grinding method may include at least one of sand milling, high energy ball milling, vibration milling, wall breaking machine grinding, and soybean milk machine grinding. It is understood that grinding includes but is not limited to the above methods, and any method that can achieve grinding of the material is acceptable.

[0028] In some embodiments, the rotation speed of the first grinding can be 500 rpm to 800 rpm, which can effectively promote uniform mixing of materials, refine particles to control particles within a suitable particle size range, optimize surface properties of particles, and enhance surface reactivity of particles, thereby further improving the electrochemical performance and structural stability of the prepared LMFP positive electrode material. The rotation speed of the first grinding can further be 650 rpm to 800 rpm, and can be 500 rpm, 600 rpm, 700 rpm or 800 rpm, etc.

[0029] For example, the one-step grinding can be a two-step grinding method using sand milling, specifically, the mixed material is introduced into a sand mill, firstly coarsely ground (the diameter of the added zirconium beads is about 0.6 mm), and then finely ground (the diameter of the added zirconium beads is about 0.3 mm). The particle size of the first slurry can be better controlled by two-step sand milling.

[0030] In some embodiments, the particle size Dv50 of the first slurry may be 0.4 μm to 1.0 μm, which is conducive to improving the particle dispersibility and specific surface area of ​​the first slurry. The Dv50 of the first slurry may further be 0.5 μm to 0.8 μm, and may be 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm or 1.0 μm, etc.

[0031] In some embodiments, the magnesium source may include at least one of magnesium hydroxide, magnesium carbonate, magnesium chloride, magnesium oxide, and the like.

[0032] In some embodiments, the manganese source may include at least one of manganese carbonate, manganese oxalate, manganese phosphate, manganese dioxide, and manganese tetraoxide.

[0033] In some embodiments, the iron source may include at least one of ferrous oxide, ferrous oxalate, ferric carbonate, and ferric phosphate.

[0034] In some embodiments, the first phosphorus source may include at least one of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, iron phosphate, manganese phosphate, and the like.

[0035] In some embodiments, the lithium source may include at least one of lithium hydroxide, lithium carbonate, lithium dihydrogen phosphate, lithium acetate, and the like.

[0036] In some embodiments, the first carbon source may include at least one of sucrose, glucose, citric acid, polypropylene, polyethylene glycol, and the like.

[0037] In some embodiments, an additive may be added for mixing in step S1, wherein the additive as a doping substance may contain at least one of Mg, Ti, V, Nb, W, Mo, Er, Co, Ni and Al. The introduction of the doping element may further improve the structural stability and electronic conductivity of the LMFP positive electrode material.

[0038] Step S2, sintering the first slurry once to obtain a magnesium-doped LMFP precursor.

[0039] In some embodiments, the first slurry may be spray dried before the first sintering, and spray drying is conducive to the volatilization of impurities and solvents. The spray drying air inlet temperature may be 220°C to 260°C, and the air outlet temperature may be 85°C to 110°C, which helps to increase the volatilization rate and drying degree of the first solvent and impurities during the spray drying process.

[0040] In some embodiments, the conditions for the primary sintering may include: a temperature of 500°C to 700°C, a time of 6 to 12 hours, and a heating rate of 2°C / min to 5°C / min. Under the above sintering conditions, it is beneficial for the magnesium element to be doped into the LMFP precursor nucleus to form a high-quality LMFP precursor with a stable crystal structure. In addition, the sintering atmosphere is an inert atmosphere, which is beneficial to reduce the oxidation of the metal elements in the first slurry and keep the prepared LMFP precursor composition stable.

[0041] Step S3, mixing the LMFP precursor, the second phosphorus source, the second carbon source and the niobium source and performing secondary grinding to obtain a second slurry.

[0042] The niobium element is introduced by adding a niobium source into a LMFP precursor, mixing and grinding the mixture together, thereby initially forming a coating layer containing the niobium element.

[0043] In some embodiments, the molar ratio of niobium to lithium in the second slurry can be (0.005-0.02):1, which is conducive to improving the coating effect of niobium and further enhancing the surface ion conductivity of the LMFP positive electrode material, thereby improving the rate performance and cycle performance during the preparation of the battery charge and discharge process. The molar ratio can further be (0.008-0.01):1, illustratively, it can be 0.005:1, 0.01:1, 0.015:1, 0.018:1 or 0.02:1, etc.

[0044] In some embodiments, the LMFP precursor, the second phosphorus source, the second carbon source and the niobium source can be dissolved in a second solvent and mixed evenly before grinding, which can effectively improve the mixing and grinding effects. Furthermore, the second solvent can be water.

[0045] In some embodiments, the secondary grinding method may include at least one of sand milling, high-energy ball milling, vibration milling, wall breaking machine grinding, and soybean milk machine grinding. It is understood that grinding includes but is not limited to the above methods, and any method that can achieve grinding of the material is acceptable.

[0046] In some embodiments, the secondary grinding speed can be 500 rpm to 800 rpm, which can effectively promote uniform mixing of materials, refine particles to control particles within a suitable particle size range, optimize surface properties of particles, and enhance surface reactivity of particles, thereby further improving the electrochemical performance and structural stability of the prepared LMFP positive electrode material. The secondary grinding speed can further be 650 rpm to 800 rpm, and can be 500 rpm, 600 rpm, 700 rpm, or 800 rpm, etc.

[0047] For example, the secondary grinding can be a two-step grinding method using sand milling, specifically, the mixed material is introduced into a sand mill, firstly coarsely ground (the diameter of the added zirconium beads is about 0.6 mm), and then finely ground (the diameter of the added zirconium beads is about 0.3 mm). The particle size of the second slurry can be better controlled by two-step sand milling.

[0048] In some embodiments, the Dv50 of the second slurry can be 0.2 μm to 0.8 μm, which is beneficial to improve the particle dispersibility of the second slurry and to control the particle size of the LMFP positive electrode material after sintering. The Dv50 of the second slurry can further be 0.3 μm to 0.5 μm, and can be 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm or 0.8 μm, etc.

[0049] In some embodiments, the second carbon source can also form a coating layer, which helps to reduce the agglomeration of the LMFP positive electrode material and improve the fluidity of the prepared LMFP positive electrode material.

[0050] In some embodiments, the second phosphorus source may include at least one of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, iron phosphate, manganese phosphate, and the like.

[0051] In some embodiments, the second carbon source may include at least one of sucrose, glucose, citric acid, polypropylene, polyethylene glycol, and the like.

[0052] Step S4, secondary sintering the second slurry to obtain a LMFP positive electrode material, wherein the magnesium element exists in the bulk phase of the LMFP positive electrode material in the form of doping, and the niobium element exists in the coating layer of the LMFP positive electrode material in the form of coating.

[0053] In some embodiments, the niobium element may exist in the form of LiNbO3 to form an amorphous surface coating layer, which can form a 3D diffusion channel for Li ions, thereby improving the ionic conductivity and structural stability of the LMFP positive electrode material.

[0054] In some embodiments, the second slurry can be spray dried before the secondary sintering, and spray drying is conducive to the volatilization of impurities and solvents, reducing the adverse effects on the subsequent sintering process. The spray drying air inlet temperature can be 220°C to 260°C, and the air outlet temperature can be 85°C to 110°C, which helps to increase the volatilization rate and drying degree of the second solvent and impurities during the spray drying process.

[0055] In some embodiments, the conditions for the secondary sintering may include: a temperature of 700°C to 850°C, a time of 6 to 12 hours, and a heating rate of 2°C / min to 5°C / min. Under the above sintering conditions, it is beneficial to further uniformly dope the magnesium element located in the bulk phase of the LMFP positive electrode material and optimize the crystal structure of the LMFP positive electrode material. At the same time, it is beneficial for the niobium element to form a coating layer on the surface phase of the LMFP positive electrode material, enhance the surface ion conductivity and thermal stability of the LMFP positive electrode material, thereby extending the cycle life and safety of the battery. In addition, the sintering atmosphere is an inert atmosphere, which is beneficial to reduce the oxidation of metal elements in the second slurry and maintain the stability of the composition of the prepared LMFP positive electrode material.

[0056] Compared with the prior art, the preparation method of the LMFP positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. This application realizes the co-doping and coating of magnesium in the bulk phase of LMFP positive electrode material and niobium on the surface layer through two-stage grinding and two-stage sintering processes. Among them, one grinding and one sintering process are used to dope magnesium in the bulk phase of LMFP positive electrode material, and Mg 2+ Replace part of Fe 2+ and / or Mn 2+ The Jahn-Teller effect in the LMFP cathode material is reduced, and the electronic conductivity and structural stability are improved. The secondary grinding and secondary sintering form a coating layer containing niobium on the surface of the LMFP cathode material, which improves the surface ion conductivity and specific capacity of the LMFP cathode material.

[0057] The synergistic effect of magnesium in the bulk phase of the LMFP positive electrode material and niobium in the coating layer improves the ionic conductivity, electronic conductivity and structural stability of the LMFP positive electrode material, and improves the rate performance and cycle performance of the LMFP positive electrode material. It creatively solves the pain points of the LMFP positive electrode material, such as poor conductivity and low capacity.

[0058] 2. The grinding process effectively controls the particle size of the LMFP positive electrode material. The mixture can be ground without destroying the performance of the material itself, and then further ground by a two-step method to more accurately control the particle size of the material.

[0059] 3. This preparation method is simple and efficient, which is conducive to the large-scale production of LMFP positive electrode materials and has excellent commercial prospects.

[0060] The embodiment of the present application provides a LMFP positive electrode material, which is prepared by the above-mentioned LMFP positive electrode material preparation method. The LMFP positive electrode material includes a positive electrode active material and a coating layer located on the surface of the positive electrode active material, wherein the positive electrode active material is doped with magnesium and the coating layer contains niobium.

[0061] Magnesium in the bulk phase can replace Fe 2+ and / or Mn 2+ The niobium element in the coating layer can improve the surface ion conductivity of the LMFP material, accelerate the lithium ion transmission rate, thereby accelerating the charge and discharge process, and can also form a tiny pore structure on the surface, which is beneficial to increase the specific surface area of ​​the LMFP positive electrode material and further improve the ion conductivity of the LMFP material.

[0062] In some embodiments, niobium can exist in the form of LiNbO3 to form an amorphous surface coating layer, which can form a 3D diffusion channel for Li ions, thereby improving the ionic conductivity of the LMFP positive electrode material. This structure not only enhances the ionic conductivity of the LMFP positive electrode material, but also further improves the structural stability and thermal stability.

[0063] In some embodiments, based on the total mass of the LMFP positive electrode material as 100%, the mass content of magnesium can be 0.3% to 0.9%. An appropriate amount of magnesium doping helps to reduce the Jahn-Teller effect of Mn³⁺, further improve the structural stability of the LMFP material, and thus improve the cycle life and energy density of the battery. The mass content of magnesium can further be 0.3% to 0.6%, and can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or 0.9%, etc.

[0064] In some embodiments, based on the total mass of the LMFP positive electrode material as 100%, the mass content of the niobium element can be 0.1% to 0.5%, and an appropriate amount of niobium coating can further improve the ionic conductivity, specific capacity and structural stability of the LMFP material and extend the cycle life. The mass content of the niobium element can further be 0.1% to 0.3%, and can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4% or 0.5%, etc.

[0065] Compared with the prior art, the LMFP positive electrode material provided in the embodiment of the present application has the following beneficial effects: the active substance of the positive electrode material inside the LMFP positive electrode material is doped with magnesium, and the outer coating layer contains niobium. The synergistic effect of the two elements in this structure improves the ionic conductivity, electronic conductivity, specific capacity and cycle performance of the LMFP positive electrode material.

[0066] See also Figure 2As shown, an embodiment of the present application provides an electrochemical device (such as a battery), wherein the electrochemical device 100 includes a positive electrode sheet 10, a lithium negative electrode sheet 20, a separator 30 and an electrolyte 40, wherein the separator 30 is arranged between the positive electrode sheet 10 and the lithium negative electrode sheet 20, and the positive electrode sheet 10 includes the aforementioned LMFP positive electrode material.

[0067] Compared with the prior art, the electrochemical device 100 provided in the embodiment of the present application adopts the aforementioned LMFP positive electrode material, which effectively improves the energy density, ionic conductivity and cycle stability of the electrochemical device 100, thereby enhancing the overall performance and service life, and meeting the needs of high-performance batteries.

[0068] The above-mentioned LMFP positive electrode material and its preparation method are further described below through specific examples.

[0069] Example 1 Step 1: Add 35.5 kg of manganese tetraoxide, 59.9 kg of iron phosphate, 41.2 kg of lithium dihydrogen phosphate, 15.2 kg of lithium carbonate, 5.9 kg of glucose, 1.36 kg of magnesium carbonate and 0.55 kg of titanium dioxide into 250 kg of water and mix them evenly. The mixed materials are introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm), and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3 mm), and the first slurry with a final particle size Dv50 of 0.45 μm is obtained by grinding.

[0070] Step 2: spray-dry the first slurry, with the inlet air temperature of the spray drying being 250°C and the outlet air temperature being 90°C, and then sintering once under inert atmosphere protection conditions, raising the temperature to 650°C at a rate of 3°C / min, keeping the temperature for 7 hours, and finally cooling to obtain a LMFP precursor.

[0071] Step 3: Add 100 kg of the above LMFP precursor, 0.8 kg of lithium dihydrogen phosphate, 6.0 kg of glucose, 3.0 kg of polyethylene glycol (molecular weight 6000) and 0.14 kg of niobium pentoxide into 150 kg of water and mix them evenly. The mixed materials are introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6 mm), and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3 mm) to obtain a second slurry with a final particle size Dv50 of 0.35 μm.

[0072] Step 4: spray-dry the second slurry, with the inlet air temperature of the spray drying being 250°C and the outlet air temperature being 90°C, and then perform secondary sintering under inert atmosphere protection conditions, raising the temperature to 750°C at a rate of 3°C / min, and keeping the temperature for 7 hours, and finally cool, air flow crush, sieve and remove iron to obtain the LMFP positive electrode material.

[0073] Comparative Example 1 The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that magnesium carbonate (or any other magnesium source) is not added in step 1, and niobium pentoxide (or any other niobium source) is not added in step 3. The preparation method of the remaining LMFP positive electrode materials is basically the same as that in Example 1, and will not be described in detail here.

[0074] Comparative Example 2 The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that no niobium pentoxide (or any other niobium source) is added in step 3, and the preparation method of the remaining LMFP positive electrode materials is basically the same as that in Example 1, which will not be described in detail here.

[0075] Comparative Example 3 The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that magnesium carbonate (or any other magnesium source) is not added in step 1, and the preparation method of the remaining LMFP positive electrode materials is basically the same as that of Example 1, which will not be described in detail here.

[0076] The following tests were performed on the LMFP positive electrode materials obtained in Example 1 and Comparative Examples 1-3, and corresponding test results were obtained.

[0077] 1. The pH value, specific surface area, carbon content, powder compaction density, tap density, resistivity and electrical properties of the LMFP positive electrode materials obtained in Example 1 and Comparative Examples 1-3 were tested. The results are shown in Table 1.

[0078] The specific test method is as follows: (1) pH value: According to GB / T 24533-2019, the stable pH value of LMFP cathode material in water was tested.

[0079] (2) Specific surface area: Using the nitrogen adsorption-desorption method, at liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its specific surface area and other characteristics. Combined with the law of change of adsorption amount with relative pressure during the adsorption process, the specific surface area test can be carried out.

[0080] (3) Carbon content: The carbon content of the LMFP positive electrode material is tested by infrared analysis. The sample is burned in a high-temperature, oxygen-rich state using a carbon-sulfur analyzer. The carbon element contained in it is oxidized into carbon dioxide and enters the infrared detector with the carrier gas. The carbon content is calculated by quantitatively analyzing the changes in the intensity of the infrared absorption wavelength of the carbon dioxide signal.

[0081] (4) Powder compaction density: Tested in accordance with the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals, "Determination of compaction density of lithium-ion battery positive electrode material powder".

[0082] (5) Tap density: Refer to GB / T 1033-2008 to test the tap density of LMFP positive electrode material.

[0083] (6) Powder resistivity: Tested in accordance with the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals, "Determination of Powder Resistivity of Lithium-ion Battery Positive Electrode Materials".

[0084] (7) Electrical properties: The LMFP positive electrode materials in Example 1 and Comparative Examples 1-3 were made into positive electrode sheets for button-type battery assembly. Metal lithium was used as the negative electrode material, and the assembled button-type batteries were tested.

[0085] The test steps for the first charge and discharge efficiency include: at room temperature of 25°C, charge the lithium-ion battery at a constant current of 0.1C (nominal capacity is 150mAh / g) to 4.5V, then charge at a constant voltage until the current drops to 0.05C, stop charging, and record the first charge capacity; then discharge at 0.1C to a cut-off voltage of 2.5V, record the first discharge capacity, calculate the 0.1C specific capacity of the positive electrode material based on the first discharge capacity, and calculate the first charge and discharge efficiency of the battery, i.e., the first efficiency, according to the following formula: first charge and discharge efficiency = (first discharge capacity / first charge capacity)*100%.

[0086] Repeat the above charging and discharging process once, record the 2nd charging capacity and 2nd discharging capacity, and calculate the 0.1C specific capacity of the lithium manganese iron phosphate positive electrode material with the 2nd discharge capacity. The result is as follows: Figure 3 .

[0087] Then, the above charging and discharging process was repeated once at a current of 1C, and the 2nd charging capacity and 2nd discharging capacity were recorded. The 1C specific capacity of the lithium manganese iron phosphate positive electrode material was calculated based on the 2nd discharge capacity.

[0088] The battery was tested at 45°C with a charge and discharge current of 1C and a capacity retention rate after 100 cycles from 2.5V to 4.4V. The results are as follows: Figure 4 .

[0089] Combination Figure 3As shown in Table 1, Comparative Example 1 does not contain Mg and Nb, Comparative Example 2 is only doped with Mg, and Comparative Example 3 is only coated with Nb. Compared with Comparative Examples 1-3, the bulk phase of the LMFP positive electrode material of Example 1 is doped with Mg, and the surface layer is coated with niobium. Due to the synergistic effect of Mg doping and Nb coating, the first efficiency and capacity of the battery prepared using this LMFP positive electrode material can be significantly improved, especially the discharge capacity of Example 1 at 1C rate is as high as 149.83 mAh / g, while that of Comparative Example 1 is only 143.92 mAh / g. This shows that the LMFP positive electrode material provided in the embodiment of the present application has good rate performance and specific capacity.

[0090] like Figure 4 As shown, the capacity retention rate of the battery prepared with the LMFP positive electrode material in Example 1 after 100 cycles is higher than that of Comparative Examples 1-3, which indicates that due to the synergistic effect of bulk doping of Mg and surface coating of Nb in the LMFP positive electrode material of Example 1, the cycle performance of the LMFP positive electrode material is significantly improved.

[0091] 2. The LMFP positive electrode materials obtained in Example 1 and Comparative Examples 1-3 were observed by scanning electron microscope. The results are as follows: Figure 5 shown.

[0092] By observation Figure 5 From the characterization of the morphology of the LMFP positive electrode material in Example 1, it can be seen that the particles of the LMFP positive electrode material in Example 1 are small and have a good coating effect. This fine and uniform particle structure helps to improve the surface activity of the LMFP positive electrode material, thereby improving the ion diffusion rate and reaction activity of the LMFP positive electrode material. The good coating effect on the surface of the LMFP positive electrode material is conducive to further improving the ion diffusion rate, while also being able to improve structural stability, optimize interface characteristics, and reduce side reactions with the electrolyte.

[0093] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: include: Mixing a manganese source, an iron source, a first phosphorus source, a lithium source, a first carbon source and a magnesium source and grinding them once to obtain a first slurry; Sintering the first slurry once to obtain a lithium manganese iron phosphate precursor; The lithium iron manganese phosphate precursor, the second phosphorus source, the second carbon source and the niobium source are mixed and subjected to secondary grinding to obtain a second slurry; as well as The second slurry is subjected to secondary sintering to obtain the lithium iron manganese phosphate positive electrode material, wherein the magnesium element exists in the bulk phase of the lithium iron manganese phosphate positive electrode material in the form of doping, and the niobium element exists in the coating layer of the lithium iron manganese phosphate positive electrode material in the form of coating.

2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of magnesium element to lithium element in the first slurry is (0.002-0.006):1; and / or The molar ratio of niobium element to lithium element in the second slurry is (0.005-0.02):

1.

3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The primary grinding speed is 500 rpm to 800 rpm; and / or The particle size Dv50 of the first slurry is 0.4 μm-1.0 μm.

4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The secondary grinding speed is 500 rpm to 800 rpm; and / or The particle size Dv50 of the second slurry is 0.2 μm to 0.8 μm.

5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The conditions of the primary sintering include: a temperature of 500° C. to 700° C., a time of 6 to 12 hours, and a heating rate of 2° C. / min to 5° C. / min; and / or The conditions of the secondary sintering include: a temperature of 700° C. to 850° C., a time of 6 to 12 hours, and a heating rate of 2° C. / min to 5° C. / min.

6. A lithium manganese iron phosphate positive electrode material, characterized in that: The lithium iron manganese phosphate positive electrode material is prepared by the preparation method of the lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 5, wherein the lithium iron manganese phosphate positive electrode material comprises a positive electrode active material and a coating layer located on the surface of the positive electrode active material, wherein the positive electrode active material is doped with magnesium element and the coating layer contains niobium element.

7. The lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: Niobium exists in the form of LiNbO3.

8. The lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: Taking the total mass of the lithium iron manganese phosphate positive electrode material as 100%, the mass content of the magnesium element is 0.3% to 0.9%.

9. The lithium iron manganese phosphate positive electrode material according to claim 6, characterized in that: Taking the total mass of the lithium iron manganese phosphate positive electrode material as 100%, the mass content of the niobium element is 0.1% to 0.5%.

10. An electrochemical device, characterized in that: It includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes a lithium iron manganese phosphate positive electrode material prepared by the preparation method of the lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 5 or a lithium iron manganese phosphate positive electrode material according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Preparation method of high-capacity lithium ferric manganese phosphate material

    CN115072695A

  • Lithium manganese iron phosphate material, preparation method of lithium manganese iron phosphate material, electrode plate and lithium battery

    CN117747767A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN117936773A

  • Positive electrode material and lithium ion battery

    WO2024103678A1

Cited By

  • Lithium manganese iron phosphate positive electrode material, preparation method thereof and electrochemical device

    CN121076126A

  • Niobium-doped and carbon nanotube-coated lithium iron nickel phosphate material and preparation method thereof

    CN121439757A

  • Lithium manganese iron phosphate positive electrode material, preparation method and application

    CN122393289A

  • Lithium manganese iron phosphate positive electrode active material and preparation method therefor, positive electrode sheet, lithium secondary battery, and electric device

    WO2026157136A1